2018
DOI: 10.2217/pgs-2017-0207
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Guided Warfarin Therapy: Current Status

Abstract: Warfarin pharmacogenomics has been an extensively studied field in the last decades as it is focused on personalized therapy to overcome the wide interpatient warfarin response variability and decrease the risk of side effects. In this expert review, besides briefly summarizing the current knowledge about warfarin pharmacogenetics, we also present an overview of recent studies that aimed to assess the efficacy, safety and economic issues related to genotype-based dosing algorithms used to guide warfarin therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 131 publications
0
28
0
9
Order By: Relevance
“…44 However, studies of genotype-guided warfarin dosing -arguably one of the best-known pharmacogenomic exampleshave not yielded clear guidance. 45 Assessment of common-disease risk and other uses of genomic data in healthy persons needs to be performed with the use of high-quality scientific methods despite the temptation to move rapidly toward implementation. 46 In a study of genome sequence analysis involving healthy patients, 22% had a monogenic disease risk result with uncertain clinical usefulness.…”
Section: He a Lth Y Per Sonsmentioning
confidence: 99%
“…44 However, studies of genotype-guided warfarin dosing -arguably one of the best-known pharmacogenomic exampleshave not yielded clear guidance. 45 Assessment of common-disease risk and other uses of genomic data in healthy persons needs to be performed with the use of high-quality scientific methods despite the temptation to move rapidly toward implementation. 46 In a study of genome sequence analysis involving healthy patients, 22% had a monogenic disease risk result with uncertain clinical usefulness.…”
Section: He a Lth Y Per Sonsmentioning
confidence: 99%
“…A published meta-analysis showed that warfarin was able to reduce stroke events by approximately 60% in patients with AF ( Hart et al, 2007 ). Nevertheless, this pharmacotherapy presents a narrow therapeutic index, extensive drug and food interactions and large inter-individual variability in dose requirements, with intensive monitoring necessary to be effective and avoid adverse effects ( Wells et al, 1994 ; Wan et al, 2008 ; Guyatt et al, 2012 ; Soares et al, 2012 ; Santos et al, 2013 ; Marcatto et al, 2016b ; Tavares et al, 2018 ). In this sense, a study from Lip et al investigated the incidence and risk of adverse events in a real world setting in AF patients using warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…20 The Clarification of Optimal Anticoagulation through Genetics (COAG) trial found no better outcomes using genotype-guided warfarin dosing in comparison to a clinical algorithmic approach. [31][32][33][34] However, a large proportion of the study population was African Americans, whose warfarin sensitivity polymorphisms were not included in genotyping. 35 The second review by Cavallari et al, published in 2017, revisited the debate with new evidence from the Genetics Informatics Trial (GIFT), which found that a 27% reduction in venous thromboembolism, hemorrhage, INR values >4, and death in the group that was doused with a genotype-guided approach.…”
mentioning
confidence: 99%